Source-specific multi-pathway human health risk assessment of metals present in clouds over Indian Subcontinent - Md Abu Mushtaque; Shahina Raushan Saikh; Abhishek Biswas; Gopala Krishna Darbha; Sanat Kumar Das (Environmental Advances, 2025)
Metal in the cloud is a matter of growing concern due to its adverse impact on human health on a wider scale through continental long-range transport. The present study identifies the toxic metals present in non-precipitating clouds during the onset of monsoon over the Western Ghats and Eastern Himalayas in the Indian subcontinent and quantifies their health risk factors of carcinogenic and non-carcinogenic diseases through inhalation, ingestion, and dermal absorption. Clouds over the Eastern Himalayas are found to have 1.5 times higher pollution levels due to an increase in 40-60% higher loading of toxic metals like Cd, Cu, and Zn emitted from heavy traffic and industrial emissions that cause high health risk factors for carcinogenic diseases. Children are at higher risk of 30% of such toxic metals than adults in India. Inhalation of polluted clouds over Eastern Himalayas containing high concentrations of toxic metals is the most potential route for non-carcinogenic diseases. Health risk for the occurrence of carcinogenic diseases has increased due to inhalation of dissolved Cr present in clouds. Present study highlights that Eastern Himalayas experience higher polluted clouds which contain toxic metals like Cd, Cr, Cu, and Zn coming from vehicular and industrial emissions over foothill regions, and inhalation of such polluted clouds is the potential cause of carcinogenic and non-carcinogenic diseases in India.